The importance of a drama program in cultivating soft skills: The actors studio academy as a case study / Mark Beau De Silva - Mark Beau, De Silva (2018)
The research is conducted to highlight the importance of a drama program as a tool in cultivating soft skills. The research objectives are to identify the components in the drama program that directly instil particular soft skills in the participants, and to compare and contrast the students verbal and non-verbal communication skills, before and after graduation of the drama program. The methodology of research is primarily qualitative, and depends on interviews with facilitators and participants, and observation throughout the drama program. The field of study for this study is drama in education, and the literature review focuses mainly on how the components of drama in education connect to its object of study, which is The Actors Studio Academy. The books and materials from the literature review purports that The Actors Studio Academy utilizes the drama enquiry technique, a main proponent of drama in education, which originated from the west. The topic of research for this study is soft skills, in particular the level of soft skills in young Malaysians, and how the courses at The Actors Studio provide aid in its cultivation (soft skills). As a holistic learner of drama also cultivates hard skills, it is crucial in this research to also see its (hard skills) co-relation to soft skills. The research endeavours to connect both soft skills and hard skills to the three domains of learning which are the cognitive (creative thinking), affective (emotion/ feeling), and psychomotor (physical/ kinesthesis). Once the data was collected via a mainly qualitative analysis, the research shows a positive to respond toward its hypothesis, which is; the drama programs at The Actors Studio Academy cultivates soft skills amongst its learners, through targeted lesson plans and activities aimed at grooming specific soft skills in the young learner.